Performance comparison of programming interfaces on the example of REST API, GraphQL and gRPC - Śliwa, Mariusz; Pańczyk, Beata (Journal of Computer Sciences Institute, 2021)
The article presents a comparison of the performance of three ways of implementing programming interfaces used in web applications - REST, GraphQL and gRPC. For the purposes of the research, three applications were developed, which were made in each of the indicated technologies and with the same functionalities. The applications were used for performance tests carried out with the use of the k6 tool. The applications are used to measure the execution time, performance and volume of processed data during display and adding operations. The obtained results allowed for the conclusion that the best interface in terms of performance (measured as the number of transactions per second) and server response time is REST. However, in terms of the smallest data volume, gRPC is the best choice.